Hearts beat loud [videorecording (DVD)] - Haley, Brett, 1983-; Haley, Brett, 1983-; Offerman, Nick, 1970-; Clemons, Kiersey, 1993-; Danson, Ted, 1947- (Gunpowder & Sky, 2018)
A father and his college-bound daughter form a song-writing duo.